GALVANIC MUD TREATMENT IN THE REHABILITATION OF PATIENTS WITH PAIN IN THE LOWER BACK - E. V. Filatova; Kh. M. Malayev (Исследования и практика в медицине)
Purpose. Evaluati on of the eﬀectiveness of complex restorati ve treatment with the inclusion of galvanic mud procedures in patients with pain in the lower back.Patients and methods. There were 30 patients (18 men and 12 women) with a diagnosis: lumbulgia or lumboeishalgia under observation. Patients underwent a course of rehabilitation on the basis of the Republican Hospital of Rehabilitation, Makhachkala. Against the background of standard therapy, galvanic mud procedures were included in the therapy.  The eﬀectiveness of the treatment was assessed by the control of pain assessment according to the VAS scale, the body mass index, the psychoemoti onal state of the HAM test, the tests of Schober and Thomayer were carried out.Results. After the complex treatment in patients, clinical and functional indices of the state of the neuromuscular apparatus Were noted, varying depending on gender. The results of the study showed that the intensity of the pain syndrome according to the VAS score in the compared groups before the rehabilitation diﬀered signiﬁcantly (5.4 ± 0.1 points in men and 6.16 ± 0.3 in women, (p <0.05), after completion of the course of treatment, the VAS score decreased statistically in both groups: in men 2.0 ± 0.4 points and in women 1.8 ± 0.1 points (p <0.05), but between groups of signiﬁcant diﬀerences in the quantitative assessment of pain the syndrome was not revealed. In determining the mobility of the lumbar spine, the results of the Schober test with lumbargia as in men, and women were unreliably reduced, after treatment restored within the norm: in men before treatment, 3.46 ± 1.47 cm, after 5.3 ± 0.73 cm (p < 0.05), in women before treatment 3.95 ± 0.5 cm, after 5.35 ± 0.55 cm (p < 0.05).The analysis of the dynamics of the test results of Tomayer revealed unreliably signiﬁcant diﬀerences before treatment in men = 24.8 ± 2.4 cm, in women = 21,6 ± 6,2 cm. After the course of treatment in both groups there was a signiﬁcant improvement in the indices: in men = 5.23 ± 1.44 cm (p <0.05), in women 1.45 ± 0.87 cm (p < 0,05), but at the same time a reliable diﬀerence in the indices (p < 0.01).Conclusion. The conducted research has shown that carrying out galvanic mud procedures in a complex of treatment in patients with lower back pain positively inﬂuences the restoration of lumbar vertebral segment motor activity, as well as the psychoemotional state of the patient. In this case, women are more actively reduced pain and increased motor activity, but less signiﬁcant indicators of the change in the psychological test.